Ensuring the Effectiveness of EService-Learning in Holistic Education Under Social Distancing. (December 2022) - Xiao, Chong; Wan, Kelvin; Chan, Wing-Fung Chad
Background: The worldwide pandemic has shifted eService-Learning from a pedagogical innovation into a must, challenging the applicability of frameworks and principles previously developed.Purpose: The authors aim to verify whether extreme eService-Learning can be assessed within Ma and Lo's holistic outcome framework and how to ensure its effectiveness in cultivating students roundly.Methodology/Approach: Based on a holistic outcome framework produced under traditional semesters, this study examines six Service-Learning courses. Adopting a mixed-method approach, self-reported students questionnaires (N = 497) were analyzed by paired-sample t-test and ANCOVA to compare students' Service-Learning outcomes in the traditional and pandemic periods, from which two effective courses were identified. A case study was conducted to conceptualize the good practices in extreme eService-Learning.Findings/Conclusions: Findings reveal extreme eService-Learning can enhance students' subject-related knowledge, soft skills, and civic orientation. To ensure its effectiveness in holistic education, balance between the tangibility and ambiguity in service and the harmony of individualized and collaborative learning should be planned in the curriculum and cautiously implemented.Implications: A holistic Service-Learning outcome framework is verified to be applicable in an entirely online environment. The summarized principles provide reference to practicing extreme eService-Learning under current social distancing restrictions and worth further normalizing in the post-COVID era.